The Effectiveness of the PAPEDA Warm-Up in Increasing PSTE Students' Motivation in Physical Education Lectures - Syahrir; Nur Laely; Muh. Mawardi; Emayanti Anggraeni; Mukharrar Fajdri (Journal of Education and Teaching Learning, 2026)
This study aimed to examine the effectiveness of the PAPEDA warm-up model in increasing the motivation of PGSD students in Physical Education lectures. The background of this study was the low motivation of students during conventional warm-up activities, which were considered monotonous and less engaging. This research used a quasi-experimental method with a pretest-posttest non-equivalent control group design. The participants were 59 third-semester PGSD students at Universitas Werisar, consisting of 29 students in the experimental group and 30 students in the control group. The experimental group received the PAPEDA warm-up model, while the control group received conventional warm-up activities. Student motivation was measured using an ARCS-based questionnaire covering Attention, Relevance, Confidence, and Satisfaction, with a Cronbach’s alpha reliability value of 0.89. Data were analyzed using an independent sample t-test. The results showed that the experimental group’s motivation increased by 50.3%, from 58.12 to 87.34, while the control group increased by only 11.5%, from 57.89 to 64.56. The difference was statistically significant with p<0.001. The highest increases occurred in Attention and Satisfaction. Therefore, the PAPEDA warm-up model was effective in increasing PGSD students’ motivation in Physical Education lectures.